(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
This essay explores the ways in which Indigenous issues were framed, amplified and subverted in the national discourse in the lead up to the 2016 federal election. An examination of key theories on minority group representation and participation in democratic process provides the framework through which channels for Indigenous self-determination on key political issues in the Australian context are examined.